2005
DOI: 10.1182/blood-2004-10-3991
|View full text |Cite
|
Sign up to set email alerts
|

Efficient migration of dendritic cells toward lymph node chemokines and induction of TH1 responses require maturation stimulus and apoptotic cell interaction

Abstract: IntroductionMyeloid dendritic cells (DCs) have the unique ability to activate naive T cells and, as such, can be tailored to initiate an immune response against neoantigens. 1 Once loaded with antigens in peripheral tissues, DCs must migrate to secondary lymphoid organs and reach a fully mature functional stage to recruit rare naive T cells. 2 In the past decade, in vitro-generated DCs have been involved as cell adjuvants in multiple tumor vaccination trials to trigger antitumor immune responses and tumor regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
1
21
0
1
Order By: Relevance
“…However, phenotypic characterization alone is insufficient to determine whether DC will induce tolerance or immunity 21, 22. In addition, it has been suggested that irrespective of the desired therapeutic outcome (induction of tolerance for prevention of autoimmune disease or immunity for treatment of cancer) DC activation is essential for the effectiveness of immunotherapy as activated DC preferentially migrate from the peripheral tissues into the draining lymph nodes where antigen‐specific interaction with T cells occurs 23, 24, 25…”
Section: Introductionmentioning
confidence: 99%
“…However, phenotypic characterization alone is insufficient to determine whether DC will induce tolerance or immunity 21, 22. In addition, it has been suggested that irrespective of the desired therapeutic outcome (induction of tolerance for prevention of autoimmune disease or immunity for treatment of cancer) DC activation is essential for the effectiveness of immunotherapy as activated DC preferentially migrate from the peripheral tissues into the draining lymph nodes where antigen‐specific interaction with T cells occurs 23, 24, 25…”
Section: Introductionmentioning
confidence: 99%
“…However, it also appears likely that infected cells dying during the course of infection may release both antigen and cellular debris, which could then be taken up by DC and used, together with either bacterial or cellular danger signals [153][154][155], to initiate a T cell response. Although DC can phagocytose chlamydiae and present chlamydial antigens to T cells [156,157], antigens provided by dying cells might be more readily accessible, as apoptotic cells are also transported along the lymphatic vessels and can be processed in lymph nodes [144,158].…”
Section: Immunological Significance Of Cell Death During Chlamydial Imentioning
confidence: 99%
“…2,8,9 DCs undergo a differentiation process during which they acquire antigens, migrate to lymphoid tissues and enhance T-cell activation potential. 10 Several stimuli are responsible for DC maturation such as pathogen components or host molecules associated with inflammation. 11 With the increasing development of vaccine strategies to manipulate immunity in a variety of diseases, there is a strong interest in defining protocols and reagents that allow optimal production of DCs from peripheral blood monocytes and define culture conditions that can minimize variability of the cell product.…”
mentioning
confidence: 99%